Sacral insufficiency fractures after high-dose carbon-ion based radiotherapy of sacral chordomas - Bostel, Tilman; Nicolay, Nils; Welzel, Thomas; Bruckner, Thomas; Mattke, Matthias; Akbaba, Sati; Sprave, Tetyana; Debus, Jürgen; Uhl, Matthias (Radiation oncology, 2018)
This study aimed to analyse the frequency and clinical relevance of sacral insufficiency fractures (SIFs) after high-dose carbon-ion based irradiation of sacral chordomas.